2018
DOI: 10.1111/jgs.15679
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific Symptoms Lack Diagnostic Accuracy for Infection in Older Patients in the Emergency Department

Abstract: Objectives To determine if nonspecific symptoms and fever affect the posttest probability of acute bacterial infection in older patients in the emergency department (ED). Design Preplanned, secondary analysis of a prospective observational study. Setting Tertiary care, academic ED. Participants A total of 424 patients in the ED, 65 years or older, including all chief complaints. Measurements We identified presence of altered mental status, malaise/lethargy, and fever, as reported by the patient, as documented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 50 publications
0
42
0
Order By: Relevance
“…The clinical conundrum of the abnormal urinalysis in an elderly patient presenting with non-specific symptoms is a common occurrence 14. While it is well-known that UTIs can cause malaise and mental status changes in elderly populations,15 consistent clinical data suggest that the overwhelming percentage of “positive” urinalyses (UA) represent asymptomatic bacteriuria, and are neither truly indicative of UTI nor related to the patient’s non-specific complaints 16. Additionally, fixating on the “positive” UA can often cause clinicians to reach premature diagnostic closure and stop further investigations.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical conundrum of the abnormal urinalysis in an elderly patient presenting with non-specific symptoms is a common occurrence 14. While it is well-known that UTIs can cause malaise and mental status changes in elderly populations,15 consistent clinical data suggest that the overwhelming percentage of “positive” urinalyses (UA) represent asymptomatic bacteriuria, and are neither truly indicative of UTI nor related to the patient’s non-specific complaints 16. Additionally, fixating on the “positive” UA can often cause clinicians to reach premature diagnostic closure and stop further investigations.…”
Section: Resultsmentioning
confidence: 99%
“…Even though certain markers defining influenza-like illness, such as fever, myalgia, chills, and cough, were somewhat predictive of positive swab results in our setting, nonspecific symptoms, such as weakness and confusion [ 16 ] were similarly predictive. Although we previously demonstrated that nonspecific symptoms such as weakness are associated with unfavorable prognosis [ 17 ], these symptoms do not generally increase the probability of infection in (older) adults in the ED [ 18 , 19 ]. These symptoms appear to be unable to distinguish COVID-19 from other (infectious) illness.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations: first, although we included a comprehensive set of diagnostic codes of infectious disease to define sepsis, the incidence of sepsis in the elderly population might be nonetheless underestimated. Because of immune failure and functional decline, conventional clinical symptoms of inflammatory response may be lacking in older patients, or they might occur with atypical manifestations, like delirium or falls [26], which are frequent confounders for the rapid diagnosis of sepsis. Second, we used the all-cause mortality rather than sepsis-related mortality as primary endpoint of our study.…”
Section: Discussionmentioning
confidence: 99%